The Association of Electronic Cigarette Use With SARS-CoV-2 Infection and COVID-19 Disease Severity. (14th April 2022) - Burnett-Hartman, Andrea N; Goldberg Scott, Shauna; Powers, J David; Clennin, Morgan N; Lyons, Jason A; Gray, Mark; Feigelson, Heather Spencer
BACKGROUND: Although combustible cigarette use is an established risk factor for severe COVID-19 disease, there is conflicting evidence for the association of electronic cigarette use with SARS-CoV-2 infection and COVID-19 disease severity. METHODS: Study participants were from the Kaiser Permanente Research Bank (KPRB), a biorepository that includes adult Kaiser Permanente members from across the United States. Starting in April 2020, electronic surveys were sent to KPRB members to assess the impact of the COVID-19 pandemic. These surveys collected information on self-report of SARS-CoV-2 infection and COVID-related risk factors, including electronic cigarette and combustible cigarette smoking history. We also used electronic health records data to assess COVID-19 diagnoses, positive PCR lab tests, hospitalizations, and death. We used multivariable Cox proportional hazards regression to calculate adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) comparing the risk of SARS-CoV-2 infection between individuals by e-cigarette use categories (never, former, and current). Among those with SARS-CoV-2 infection, we used multivariable logistic regression to estimate adjusted odds ratios (ORs) and 95% CIs comparing the odds of hospitalization or death within 30 days of infection between individuals by e-cigarette use categories. RESULTS: There were 126, 475 individuals who responded to the survey and completed questions on e-cigarette and combustible cigarette use (48% response rate). Among survey respondents, 819 (1%) currently used e-cigarettes, 3, 691 (3%) formerly used e-cigarettes, and 121, 965 (96%) had never used e-cigarettes. After adjustment for demographic, behavioral, and clinical factors, there was no association with SARS-CoV-2 infection and former e-cigarette use (hazard ratio (HR) = 0.99; CI: 0.83–1.18) or current e-cigarette use (HR = 1.08; CI: 0.76–1.52). Among those with SARS-CoV-2 infection, there was no association with hospitalization or death within 30 days of infection and former e-cigarette use (odds ratio (OR) = 1.19; CI: 0.59–2.43) or current e-cigarette use (OR = 1.02; CI: 0.22–4.74). CONCLUSIONS: Our results suggest that e-cigarette use is not associated with an increased risk of SARS-CoV-2 infection or severe COVID-19 illness.